The Nature of the Chemical Bond from a Quantum Mechanical Interference Perspective. Issue 2 (13th January 2017) - Fantuzzi, Felipe; de Sousa, David Wilian Oliveira; Nascimento, Marco Antonio Chaer
Abstract: The analysis of the chemical bond in a variety of systems exhibiting distinct bonding patterns was performed using the Generalized Product Function Energy Partitioning (GPF‐EP) approach in order to verify the role played by quantum interference. Diatomic and polyatomic molecules, with single, double and triple bonds, with different degrees of polarity, linear or branched, cyclic or not, conjugated and aromatics, have been considered. In all cases the conclusion was exactly the same: for each bond of the molecule the energy partitioning results showed that the main contribution to the depth of the potential wells comes from the interference term. From the quantum interference perspective the minimum requirement for a chemical bond to be formed is one electron and two interfering one‐electron states belonging to different atoms. As a consequence, all chemical bonds are covalent in the sense that it takes a one‐electron state of each atom to form the bond, irrespective of its polarity. Abstract : A unified description: Chemical bonding, irrespective of its polarity, is the result of modifications in the electronic density caused by the quantum interference effect. The minimum requirement for a chemical bond to be formed is one electron and two interfering one‐electron states belonging to different atoms. Therefore, the interference energy analysis leads to a unified view of the chemical bonding concept.